2022
DOI: 10.3390/foods11040607
|View full text |Cite
|
Sign up to set email alerts
|

Varied Effects of COVID-19 Chemosensory Loss and Distortion on Appetite: Implications for Understanding Motives for Eating and Drinking

Abstract: A common symptom of COVID-19 is altered smell and taste. This qualitative study sought to further characterise this altered chemosensory perception and its effects on appetite for food and drink. Eighteen women and two men who had experienced chemosensory loss associated with COVID-19 participated in semi-structured interviews. Thematic analysis of the interview transcripts revealed five major themes. These confirmed that all participants had experienced an altered sense of smell (anosmia, and less frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…In our study, a lower proportion than the COVID-19 sample, 33% of the healthy sample, reported having skipped meals. These results are consistent with previous studies [ 35 , 36 ] indicating that COVID-19 infection is associated with a change in eating habits, which could also be related to emotional aspects such as anxiety [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, a lower proportion than the COVID-19 sample, 33% of the healthy sample, reported having skipped meals. These results are consistent with previous studies [ 35 , 36 ] indicating that COVID-19 infection is associated with a change in eating habits, which could also be related to emotional aspects such as anxiety [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a more recent study, twenty subjects (eighteen women and two men) who experienced chemosensory loss associated with SARS-CoV-2 infection underwent a semi-structured interview, which consisted of several open questions focused on five major themes concerning the nature of altered chemosensory perception and consequent changes in appetite, experiences of eating, eating behaviour, and well-being [ 53 ]. The study results were not quantitative but qualitative.…”
Section: Variations In Eating Habits and Body Weight Due To Covid-19-...mentioning
confidence: 99%
“…The “wanting” component of food reward, related to the post-ingestion detection of nutrients during the meal, was unchanged (the participants referred to this as “mindless eating”) and accounted for a bidirectional trend in body weight change by inducing both the loss and increase of weight (only six participants reported weight loss). An increase in alcohol intake was mentioned by some participants, in part due to the reduced intensity of the perception of alcohol’s disliked flavour [ 53 ]. The generalisability of the study’s findings was limited due to the low number of participants involved.…”
Section: Variations In Eating Habits and Body Weight Due To Covid-19-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, crunchy solid foods (ie, grains, cereals, hard vegetables, and crispy snacks) may be beneficial for COVID-19/PASC patients 42 . Furthermore, different food textures combined with strong flavors (ie, pepper, wasabi, ginger) and spices (ie, cinnamon, vanilla, chili) could provide additional organoleptic attributes for increasing gastronomic pleasure 37,55 …”
Section: Management Of Csd In Covid-19/pascmentioning
confidence: 99%